PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBASIS QUIZIZZ PAPER MODE TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS XI SMA DARUSSALAMAH BRAJA DEWA - Niken Komala Sari; HRA Mulyani; Muhfahroyin (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to determine the effect of the Problem Based Learning (PBL) model based on Quizizz Paper Mode on student learning outcomes in the human digestive system material in class XI SMA Darussalamah Braja Dewa. This type of research is a quasi-experimental. The research location was SMA Darussalamah Braja Dewa. The population in this study were all students of class XI SMA Darussalamah Braja Dewa. The samples used in this study were two classes, namely XI 1 as the control class using the Problem Based Learning (PBL) model without additional media, and XI 2 as the experimental class using the Problem Based Learning (PBL) model based on Quizizz Paper Mode. The prerequisite tests in this study used the normality test and the homogeneity test. Hypothesis testing used the t-test. The results showed that the average learning outcomes in the experimental class (79.66) were significantly higher than in the control class (65.6). This is evidenced by the results of the two-mean difference test, where t-count (20,82) > t-table (2,011). Thus, the application of the Problem Based Learning (PBL) model based on Quizizz Paper Mode affects student learning outcomes in the human digestive system material for class XI SMA Darussalamah Braja Dewa.”